Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Organisasi Lembaga Mahasiswa UST Dengan Motivasi Sebagai Variabel Moderasi - Dewi Kusuma Wardani; Leni Mulyani (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This research aims to test whether the participation of budgeting in the organization of UST student institutions affects organizational performance through motivation. Research data uses direct/primary data. The sampling method used is convenience sampling. Data analysis techniques are path analysis, in which budgeting participation becomes independent variables, organizational performance becomes dependent variables, and motivation as moderation variables. The results of the analysis concluded that the participation of budget preparation had no effect on organizational performance, motivation could not strengthen the positive influence of budget preparation participation on organizational performance. The implication of this study is that budgeting participation is not the only element that plays an important role in the process of developing organizational performance in the organization of UST Yogyakarta student institutions